ON THE THEORETICAL BASING THE DIRECTION DEPENDENCE COSMOLOGICAL DECELERATION PARAMETER - Chechin, L. M. (Одеські астрономічні публікації, 2012)
For theoretical describing the asymmetry of Hubble's diagrams and calculating the anisotropy of deceleration parameter phenomenon the concepts of Universe rotation and its two-component model were involved. Our result (Δq/q0)max ≤ 0.48 is in good correlation with the value (Δq/q0)max = 0.76 -0.46 +0.41 in (Cai & Tuo, 2011).